RAMRSP AIRLINE TICKET SALES SYSTEM DESIGN - Nasution, Ahmad Rizki Marganti; Sendi Al Fadil; Ryan Aulia Amanda; Ahmad Muchlis; Muhammad Angga Syahputra; Putri Nabila (INFOKUM, 2023)
The RAMRSP Airplane Ticket Sales System Design is an exploratory study aimed at developing an airplane ticket sales platform to enhance efficiency and integration in the flight ticket booking process. This system presents solutions that encompass a variety of outstanding features, such as accurate route search capabilities, ticket choices from various airlines, secure payment methods, as well as integration with travel agents and various payment options. Moreover, the system also pays attention to purchase notifications and confirmations, along with customer data management, to ensure an optimal ticket booking experience. At its core, the emphasis in this system design lies in stringent data security aspects, scalability capabilities, and a user-friendly interface. By adopting this holistic approach, it is expected that the system will deliver an integrated and secure experience for users throughout the airplane ticket booking process.